Th17 and Th1 Lymphocytes Are Correlated with Chronic Periodontitis. (2nd April 2016) - Chen, Xiao-Tao; Chen, Li-Li; Tan, Jing-Yi; Shi, Dan-Hui; Ke, Ting; Lei, Li-Hong
ABSTRACT: T cells are involved in the homeostasis of periodontal tissues and mediate bone loss in periodontitis, but the involvement of T-helper cells in chronic periodontitis (CP) in a Chinese population is still unclear. This study aimed to assess the distribution of peripheral and local T helper (Th17) and Th1 in CP. Sixty-eight patients with CP and 43 healthy controls were recruited from April 2012 to July 2014 at the Department of Stomatology, People's Hospital of Xinjiang Uygur Autonomous Region (China). The proportions of Th17 (CD3 + CD4 + IL-17 + ) and Th1 (CD3 + CD4 + IFN-γ + ) T-cells in peripheral blood samples were assessed by flow cytometry. Immunohistochemistry was used to quantify interleukin-17 (IL-17) and interferon-gamma (IFN-γ) protein levels in gingival biopsy samples. mRNA levels of IL-17, IFN-γ RORγt, and T-bet in gingival biopsy samples were measured by quantitative real-time polymerase chain reaction (qRT-PCR). The proportions of circulating Th17 cells and Th1 cells were both more abundant in CP patients than in controls (Th17: 1.05% ± 0.87% vs. 0.62% ± 0.49%, P < 0.01; Th1: 13.93% ± 7.94% vs . 8.22% ± 4.50%, P < 0.001). Positive correlations were obtained between the proportion of circulating Th17 cells and probing depth (PD) (r = 0.320, P = 0.001) and between the proportion of circulating Th1 cells and PD (r = 0.372, P < 0.001). IL-17 and IFN-γ protein levels in gingival biopsy samples were markedly increased in CP compared to controls (both P < 0.05). Relative IFN-γ, IL-17A, and T-bet mRNA levels in CP biopsies were higher compared to controls (all P < 0.05). These results suggest that elevated peripheral and local Th17 and Th1 cells might be involved in the pathogenesis of CP.